Predictors of functional outcome in non-operatively managed Achilles tendon ruptures. Issue 4 (August 2018) - Aujla, Randeep; Patel, Shakil; Jones, Annette; Bhatia, Maneesh
Highlights: Dynamic full-weight bearing treatment regimens for acute Achilles tendon rupture provide good functional outcomes. Increasing age and female gender lead to statistically poorer functional scores. There is no significant change in function following non-surgical treatment of acute Achilles tendon ruptures after 8 months. Abstract: Background: Acute Achilles tendon (AT) rupture management remains debatable but non-operative functional regimes are beginning to gain popularity. The aim of this study was to identify predictors of functional outcome in patients with AT ruptures treated non-operatively with an immediate weight bearing functional regime in an orthosis. Methods: Analysis of prospectively gathered data from a local database of all patients treated non-operatively at our institution with an AT rupture was performed. For inclusion in the study patients required a completed Achilles Tendon Rupture Score (ATRS) at a minimum of 6 months post injury. The ATRS score was correlated against age, gender, time following rupture, duration (8 or 11 weeks) of treatment in a functional orthoses and complications were recorded. Results: 236 patients of average age 49.5 years were included. The mean ATRS on completion of rehabilitation was 74 points. The mean ATRS was significantly lower in the 37 females (65.8) as compared to the 199 males (75.6) (p = 0.013). Age inversely affected ATRS with a Pearsons correlation of −0.2. There was no significant difference in the ATRS score when comparing the two different treatment regime durations. There were 12 episodes of VTE and 4 episodes of re-rupture. The ATRS does not change significantly after 6 months following rupture treatment completion. Conclusion: Patients with AT ruptures treated non-operatively with a functional rehabilitation regime demonstrate comparable function to other non-surgical regimes with low re-rupture rates. Increasing age and female gender demonstrate inferior functional outcomes. Clinical relevance: Females and increasing age predict poorer functional outcome in acute Achilles tendon ruptures managed in a dynamic full-weight bearing treatment regime.